2015
DOI: 10.1515/hppj-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Degradation profile and safety evaluation of methomyl residues in tomato and soil

Abstract: Summary A high performance liquid chromatography with the photodiode array detector (HPLCDAD) analytical method was developed to determine the residue levels and investigate the dissipation pattern and safety use of methomyl in tomato and soil. Methomyl residues were extracted from tomato and soil samples with ethyl acetate. The extract was cleaned up with the QuEChERS method. The results showed that the average recoveries were in the range of 87.1-94.5%, with RSD of 6.9-11.2%. Limits of detection (LOD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(20 reference statements)
3
4
1
Order By: Relevance
“…In the present study, the residue concentrations of methomyl, at 2.6 mg kg -1 , were below the MRL 1 day after treatment (Table 2); at 5.1 days, its half-life is in agreement with results obtained by Reeve et al (1992), which showed that variable half-lives of methomyl in grape foliage in 36 U.S. fi elds ranged from 1 to 7.7 days. In contrast, the half-life of methomyl in qat leaves, as demonstrated in our study, is longer than the reported half-lives in other studies of other plants e.g., 0.9-1.34 days for tomatoes (Gambacorta et al, 2005;Malhat et al, 2015) and 0.88-0.94 days for okra fruits (Aktar et al, 2008). The half-life of methomyl in plants increases signifi cantly with the progression of the summer months (Reeve et al, 1992) due to the slow growth of plants and, consequently, less effi ciency in the degradation of the pesticides.…”
Section: Resultscontrasting
confidence: 81%
“…In the present study, the residue concentrations of methomyl, at 2.6 mg kg -1 , were below the MRL 1 day after treatment (Table 2); at 5.1 days, its half-life is in agreement with results obtained by Reeve et al (1992), which showed that variable half-lives of methomyl in grape foliage in 36 U.S. fi elds ranged from 1 to 7.7 days. In contrast, the half-life of methomyl in qat leaves, as demonstrated in our study, is longer than the reported half-lives in other studies of other plants e.g., 0.9-1.34 days for tomatoes (Gambacorta et al, 2005;Malhat et al, 2015) and 0.88-0.94 days for okra fruits (Aktar et al, 2008). The half-life of methomyl in plants increases signifi cantly with the progression of the summer months (Reeve et al, 1992) due to the slow growth of plants and, consequently, less effi ciency in the degradation of the pesticides.…”
Section: Resultscontrasting
confidence: 81%
“…Studies indicated that tomato treated with methomyl should remain in the field about 15 days before harvesting in order to be consumed and marketed safely for human consumption. These results are in agreement with Malhat et al (2015) who calculated residue half-life of methomyl in tomato fruits as 1.34 days. Since methomyl has a systemic action, it can migrate inside the cuticle of the tomatoes and it may create different bonds with the inner media compounds of tomatoes (Rasolonjatovo et al 2017).…”
Section: Dissipation Of Methomyl Residues In Tomato Fruitssupporting
confidence: 93%
“…The observed DT50 of methomyl observed on spinach (3.11days) fits into the range of half-lives of methomyl on growing foliage (1-7 days) reported by [23,31]. Also, methomyl half-lives were 1.34 and 1.1867days on tomato fruits [3,20].…”
Section: Dissipation Of Chlorfenapyr and Methomyl In Spinachsupporting
confidence: 74%